Anchors away? The impacts of anchor scour by ocean-going vessels and potential response options. (November 2016) - Davis, Andrew R.; Broad, Allison; Gullett, Warwick; Reveley, James; Steele, Chantel; Schofield, Clive
Abstract: Shipping is critical to global trade and anchoring is a long-held practice for safe and effective ship operations. While it is well established that anchoring or mooring of small recreational vessels has physical impacts on the seafloor and associated biota, the impacts of larger ships on seafloor environments has received little attention. This is, however, an increasingly pressing issue as world trade increases and shipping impacts on valuable yet vulnerable marine environments escalate. Using a case study in south eastern Australia this article highlights the multifaceted issues surrounding the anchoring of large ocean-going vessels. How these activities interact with marine environments is explored, with emphasis on the significant uncertainty surrounding impacts on seafloor biota. Finally, a range of potential response options to mitigate the effects of anchoring are provided. Highlights: A growing global shipping fleet (>65, 000) routinely anchor while waiting to berth. The unregulated anchoring of ocean-going vessels risks significant seafloor damage. This issue is shrouded in jurisdictional complexity affecting numerous stakeholders. Mitigating the impacts of anchor scour requires a multifaceted approach. Designated anchorages that have been assessed biologically may offer a solution.